Assay of urinary 8-hydroxy-2'-deoxyguanosine by capillary electrophoresis with spectrophotometric detection using a high-sensitivity detection cell and solid-phase extraction - Petrů, Klára; Siroká, Jitka; Bydžovská, Lucie; Krčmová, Lenka; Polášek, Miroslav (Electrophoresis, 2014)
A sensitive capillary electrophoretic method featuring spectrophotometric detection using a commercial Z-cell was devised for the assay of 8-hydroxy-2'-deoxyguanosine (8OHdG) in human urine. Solid-phase extraction (SPE) based on hydrophilic-lipophilic-balanced RP sorbent was utilized for urine sample pretreatment and analyte preconcentration. The separation was carried out in conventional fused-silica capillaries employing a Z-cell with hydrodynamic sample injection (at 50 mbar for 12 s). The BGE (pH* 9.2, adjusted with 1 M NaOH) contained 0.15 M boric acid and 10% v/v ACN. The detection wavelength was 282 nm. The calibration curve for 8OHdG (measured in spiked urine) was linear in the range 10-1000 ng/mL; R(2) = 0.9993. The LOD was 3 ng/mL (11 nmol/L) of 8OHdG. Determination of the 8OHdG urinary levels was possible even in healthy individuals.
Keywords: CE; deoxyguanosin; Solid Phase Extraction; Electrophoresis, Capillary; 8-Hydroxy-2′-deoxyguanosine; 8-hydroxy-2'-deoxyguanosin; Linear Models; elektroforéza kapilární; Reproducibility of Results; lidé; Deoxyguanosine; lineární modely; 8-Hydroxy-2'-Deoxyguanosine; reprodukovatelnost výsledků; limita detekce; Oxidative stress; extrakce na pevné fázi; Limit of Detection; Urine; Humans